2001
DOI: 10.1111/0022-4537.00222
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Immigration Policy Orientations Among Dominant‐Group Members in Western Europe

Abstract: Predictors of immigration policy attitudes were investigated among members of receiving societies in large national probability samples in 15 Western European countries. We found that a considerable proportion of the variation in immigration policy orientations toward outgroups could be explained by self-and group interests and independent measures of perceived threat. Self-reported racism also contributed independently and significantly to these policy positions. It was concluded that a general framework of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 24 publications
3
98
0
9
Order By: Relevance
“…(e.g., Hinkle & Brown, 1990;Jackson, Brown, Brown, & Marks, 2001;Pehrson, Brown, & Zagefka, 2009). It seems that it is the narcissistic, exaggerated group esteem that is reliably related to intergroup hostility in Germany analyzed by Theodore Adorno).…”
Section: Running Head: Collective Narcissism In Group Image Threat Amentioning
confidence: 99%
“…(e.g., Hinkle & Brown, 1990;Jackson, Brown, Brown, & Marks, 2001;Pehrson, Brown, & Zagefka, 2009). It seems that it is the narcissistic, exaggerated group esteem that is reliably related to intergroup hostility in Germany analyzed by Theodore Adorno).…”
Section: Running Head: Collective Narcissism In Group Image Threat Amentioning
confidence: 99%
“…Negative outcomes of immigrant presence can furthermore be anticipated on the individual or the collective level, reflecting motivations of individual or collective selfinterest (e.g., Burns & Gimpel, 2000;Citrin, Green, Muste, & Wong, 1997;Jackson, Brown, Brown, & Marks, 2001;Stephan & Renfro, 2003). Individual threat perceptions describe situations where members of the receiving society are concerned that their individual interests are menaced by immigration.…”
Section: Majority Attitudes Towards Immigration: Threat Perspectivesmentioning
confidence: 99%
“…In Britain, Lynn and Lea (2003), for example, showed that current ideas of citizenship and national identity are part of a public discourse that contributes to a 'new Apartheid. ' A variety of theories suggest that fear and perceptions of threat play an important role in generating prejudice toward out-groups in general, and toward immigrant groups in particular (e.g., Esses, Dovidio, Jackson, & Armstrong, 2001;Jackson, Brown, Brown, & Marks, 2001). Different types of threat have been identified, such as realistic and symbolic threat (Stephan & Stephan, 1996) and the perception of these threats can lead to negative reactions toward immigrants and minorities.…”
Section: Out-group Threatmentioning
confidence: 99%